2007
DOI: 10.1002/mma.849
|View full text |Cite
|
Sign up to set email alerts
|

Controllability of the nonlinear Schrödinger equation in the vicinity of the ground state

Abstract: SUMMARYLocal exact controllability of the one-dimensional NLS (subject to zero-boundary conditions) with distributed control is shown to hold in a H 1 -neighbourhood of the nonlinear ground state. The Hilbert Uniqueness Method (HUM), due to Lions, is applied to the linear control problem that arises by linearization around the ground state. The application of HUM crucially depends on the spectral properties of the linearized NLS operator which are given in detail. INTRODUCTIONThe control properties of many pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…For nonlinear equations, we refer to [34] by Dehman, Gérard, Lebeau, [42] by Lange Teismann, [46,45] by Laurent, [57] by Rosier, Zhang.…”
Section: Controllability Results For Schrödinger and Wave Equationsmentioning
confidence: 99%
“…For nonlinear equations, we refer to [34] by Dehman, Gérard, Lebeau, [42] by Lange Teismann, [46,45] by Laurent, [57] by Rosier, Zhang.…”
Section: Controllability Results For Schrödinger and Wave Equationsmentioning
confidence: 99%
“…They showed that the system (1.4)-(1.5) is locally exactly controllable in the space H 1 p (−π , π) := {v ∈ H 1 (−π , π): v(−π ) = v(π )}. Later, Lange and Teismann [11] (1. 6) They showed that the system (1.4)-(1.6) is locally exactly controllable in the space H 1 0 (0, π) around a special ground state of the system.…”
Section: Introductionmentioning
confidence: 98%
“…Let v m be the classical solution of problem (12)- (14) in the domain Q and let conditions 1° and 2°° be satisfied. Then the following estimate is true for v m :…”
Section: Estimates For the Solutions Of Boundary-value Problems With mentioning
confidence: 99%